Chiral Phosphoric Acid Catalyzed Stereoselective Spiroketalizations - Nagorny, Pavel; Sun, Zhankui; Winschel, Grace A. (Synlett, 2013)
The spiroketal functionality is an important structural motif present in numerous natural products. The synthesis of chiral spiroketals is typically achieved under equilibrating conditions and only few asymmetric approaches are known. We have demonstrated that chiral phosphoric acids (CPAs) could serve as effective catalysts for enantioselective spiroketalizations as well as control the course of the corresponding diastereoselective reactions.
Keywords: acetals; spiro compounds; asymmetric catalysis; oxocarbenium ion; enantioselectivity; diastereoselectivity; chiral phosphoric acids